Occipital condyle screws: indications and technique - Bosco, Aju (J Spine Surg, 2020)
Occipitocervical instability is a life threatening and disabling disorder caused by a myriad of pathologies. Restoring the anatomical integrity and stability of the occipitocervical junction (OCJ) is essential to achieve optimal clinical outcomes. Surgical stabilization of the OCJ is challenging and technically demanding. There is a paucity of options available for anchorage in the cephalad part of the construct in occipitocervical fixation systems due to the intricate topography of the craniocervical junction combined with the risk of injury to the surrounding anatomical structures. Surgical techniques and instrumentation for stabilizing the unstable OCJ have undergone several modifications over the years and have primarily depended on occipital squama-based fixations. At present, the occipital-plate-screw-rod construct is the most commonly adopted technique of stabilizing the OCJ. In certain distinct scenarios like posterior fossa craniectomy (absence of occipital squama for screw placement), malignancy and infection of occipital squama (poor screw purchase in the diseased occipital bone) and in revision surgery for failed occipitocervical stabilization, occipital plate-based instrumentation is not feasible. To overcome these difficulties, recently, a novel technique of occipitocervical stabilization, using the occipital condyle (OC) as the cephalad anchor, namely the direct occipital condyle screw (OCS) fixation was described. Several cadaveric and biomechanical studies have suggested that OCSs are feasible options as additional augmentative anchors in a standard occipital plate-screw-rod construct or as salvage cephalad anchors in previous failed occipital-plate-screw-rod constructs. The OCS placement technique has a steep learning curve. We have done a review of the techniques of OCS fixation and have described the indications, biomechanical and technical considerations, preoperative planning, surgical technique, complications, advantages and limitations of OCS based occipitocervical fixation.